An Atypical Presentation of Acute Pulmonary Embolism With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Pneumonia - Elavia, Nasha (Cureus, 2020)
Clinical presentation and severity of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) varies greatly amongst patients, as supported by recent literature. This poses an ongoing challenge in the diagnostic and therapeutic approach for managing these patients. Here, we would like to describe a case of acute bilateral pulmonary embolism (PE) presenting with atypical gastrointestinal symptoms in a patient with SARS-CoV-2 infection. This atypical presentation of PE is unique to our case and highlights the significance of a high index of clinical suspicion for SARS-CoV-2 and its associated thrombogenic effect, even in patients with atypical symptoms.